Análisis de los contenidos de entretenimiento de los influencer de Babahoyo en el 2022. Caso Juanka - Beltran Romero, Kevin Armando (2023)
The present study analyzes the entertainment content of Babahoyo influencers in 2022. Juanka Case, aims to analyze the entertainment content of Babahoyo influencers in 2022. Juanka Case, in which the presence of influencers stands out. in social networks, identifies their actions and describes the content used by them and especially the Babahoyense influencer Juanka, the case study is oriented towards basic research, adopts a descriptive design with a qualitative approach, intended for the analysis of data from the units of information that is complemented by the use of the inductive-deductive method, the observation sheet techniques to the contents published by the influencer in question and the interview with a renowned creator of digital content from Babahoyo as a way of collecting information, obtaining as results that its contents broadcast entertainment that attracts the attention of the public, largely humor with a double meaning encouraging curiosity, in addition to exposure of personal life in some cases exaggerating, the content that Juank broadcasts is considered to have given results because they have segmented the audience, they know what they consume and what they are the topics that interest them, there is entertainment content that edifies the audience and destroys or makes fun of others, generating more negative than positive situations in the audience.